2012
DOI: 10.1111/j.1468-036x.2012.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management for Italian Non‐Financial Firms: Currency and Interest Rate Exposure

Abstract: This paper surveys risk management practices among Italian non-financial firms. This paper’s contribution lies in investigating derivative usage particular to Italian businesses, a groupwhose public disclosure of derivative instruments is not routine. Italy is characterised by a high percentage of small and medium sized family run\ud firms. The survey examines determinants of currency and interest rate derivative use with respect currency and to firm size, geographical location, rating, industry, access to cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 78 publications
1
26
0
Order By: Relevance
“…Additionally, liquidity conditions in the foreign exchange market strongly correlate with equity market liquidity so that isolating pure foreign exchange risk is quite challenging (Mancini et al, 2013). Finally, the well-developed derivatives markets allow both, banks and industrials, to effectively hedge their foreign exchange exposure (Hankins, 2011;Bodnar et al, 2013). Overall, these findings suggest that foreign exchange risk represents a market-wide risk rather than an unambiguous type of bank risk and likely shares some common variation with the market risk factor.…”
Section: Foreign Exchange Riskmentioning
confidence: 79%
“…Additionally, liquidity conditions in the foreign exchange market strongly correlate with equity market liquidity so that isolating pure foreign exchange risk is quite challenging (Mancini et al, 2013). Finally, the well-developed derivatives markets allow both, banks and industrials, to effectively hedge their foreign exchange exposure (Hankins, 2011;Bodnar et al, 2013). Overall, these findings suggest that foreign exchange risk represents a market-wide risk rather than an unambiguous type of bank risk and likely shares some common variation with the market risk factor.…”
Section: Foreign Exchange Riskmentioning
confidence: 79%
“…() finds that only 60% of Dutch firms use derivatives and Bodnar et al . () finds that only 56% (65%) of Italian firms use FX (IR) derivatives.…”
Section: Sample Constructionmentioning
confidence: 99%
“…More recently, Bodnar et al . () and Jankensgård () examine Italian and Swedish firms, respectively, again using survey data. Of the previous studies that use data gathered directly from firms’ annual reports, only Muller and Verschoor () examine the determinants for an exclusively European sample, whereas Bartram et al .…”
Section: Introductionmentioning
confidence: 99%
“…Most business programs, especially finance MBA programs typically train their students in option pricing and credit risk management. Bodnar et al (2013) find a positive relationship between CEO education and the use of foreign currency derivatives. Chen et al (2013) show that CEO ability heterogeneity and board recruiting ability is negatively related to credit risk.…”
Section: Hypothesis Developmentmentioning
confidence: 78%
“…Similarly for executives, MacCrimmon and Wehrung (1990) found that Canadian executives with lower education were more risk taking than American executives or Canadian executives with higher education. There is also evidence that managers with more education are more actively involved in corporate hedging as evidenced by their increased use of derivatives (Pennings and Garcia, 2004;Bodnar et al, 2013). In addition Belghitar and Clark (2012) find a negative and significant effect between CEO education and total and idiosyncratic risk.…”
Section: Hypothesis Developmentmentioning
confidence: 99%